2020
DOI: 10.33225/jbse/20.19.804
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relations Among Pre-Service Science Teachers’ Motivational Beliefs, Learning Strategies and Constructivist Learning Environment Perceptions Through Unsupervised Data Mining

Abstract: Educational data mining is a developing research trend for exploring hidden patterns and natural associations among a set of student, teacher or school related variables. Discovering profiles of preservice science teachers using data mining methods would give important information about quality of teacher education programs and future science teachers’ performance. The aim of this research was to describe characteristics of preservice science teachers and to explore the relations among their motivational belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(72 reference statements)
0
3
0
2
Order By: Relevance
“…Virtual teaching Academic performance [51][52][53][54][55][56] Face-to-face teaching Academic performance [44], [57][58][59][60][61] Student desertion [24], [36], [62], [63] Based on the findings of the systematic review, a crosstab analysis was performed between the teaching modality and the variable under study, with respect to the teaching field. In reference to Table 5, it is shown that, from the articles reviewed to a greater extent, 37.5% apply data mining in face-to-face teaching, taking the academic performance as the study variable.…”
Section: Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…Virtual teaching Academic performance [51][52][53][54][55][56] Face-to-face teaching Academic performance [44], [57][58][59][60][61] Student desertion [24], [36], [62], [63] Based on the findings of the systematic review, a crosstab analysis was performed between the teaching modality and the variable under study, with respect to the teaching field. In reference to Table 5, it is shown that, from the articles reviewed to a greater extent, 37.5% apply data mining in face-to-face teaching, taking the academic performance as the study variable.…”
Section: Teachingmentioning
confidence: 99%
“…• Data about the student • Student performance • Student self-assessment [24], [54], [61] Data accumulated in learning platforms…”
Section: University Management System Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…El marco formativo en el que se desarrolla este proyecto se sustenta en la perspectiva constructivista sobre la formación docente, en la que se concede gran importancia a la visión personal del profesorado sobre los procesos educativos (Chen & Bonner, 2017;Kingir et al, 2020). En esta línea de trabajo se han desarrollado numerosos estudios, en los que se aprecia que los profesores y profesoras en formación muestran ideas personales sobre la docencia que influyen en la práctica educativa posterior (Fuentes et al, 2009;Hernández y Maquilón 2010).…”
Section: Introducción Y Fundamentounclassified
“…Os trabalhos incluídos na revisão também estabelecem importantes relações entre a aprendizagem estratégica e autorregulada e as variáveis acadêmicas (área de 14 conhecimento, ano do curso, tempo de estudo diário, semestre, autopercepção de desempenho e intenção de prosseguir no curso), demográficas (gênero e idade) e motivacionais e afetivas (ARCOVERDE et al, 2020;BOOM, 2020;BORUCHOVITCH et al, 2020;HÄKKINEN et al, 2020;KINGIR;GOK;BOZKIR, 2020;KÖRÜKCÜ, 2020;ÖZDEMIR;ÖNAL, 2021). Todos esses dados são valiosos, pois podem nortear ações formativas e projetos de intervenção para melhorar o uso das estratégias de estudo e aprendizagem na formação de professores, direcionando esforços para aqueles grupos mais fragilizados no que tange ao uso das estratégias (SPURK et al, 2020).…”
Section: Introductionunclassified